Anxiety and depression in elderly people living in an urban community in Kathmandu - Gorkhali, Binu; Karki, Namrata (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Ageing is associated with several risk factors such as loss of income, loss of spouse, chronic comorbidities, cognitive impairment, bereavement, living alone, decreased physical functionality, and fear of death. Consequently, mental health issues such as anxiety disorders and depression are very common. This study aimed to find the prevalence of anxiety and depression among elderly people living in a community of urban Kathmandu. Materials and Methods: Levels of anxiety and depression were assessed by interviewing elderly people living in the community of Gokarneswor-7, Kathmandu by using validated Nepali translations of Beck Anxiety Inventory and Geriatric Depression Scale respectively. Results: One hundred and eight elderly people (52 males, 48%), of mean age 68 years, all living in family, gave complete responses. Both anxiety and depression had prevalence rates of 52% and 2% for severe forms. Comorbidity was found in 36% of the elderly and another 36% had none of the disorders. Anxiety was more common in females and those with comorbid chronic diseases; other socio-demographic factors such as age, occupation, education level, ethnicity, religion, or type of family had no significant association (p>0.05). Depression showed significant association with none of these factors. Conclusion: Anxiety and depression are common among elderly people living in community in urban Kathmandu. More than one third have both disorders.